2018
DOI: 10.1093/annonc/mdy060
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the eighth TNM classification on p16-positive oropharyngeal squamous cell carcinomas in the Netherlands and the importance of additional HPV DNA testing

Abstract: TNM-8 has a better predictive prognostic power than TNM-7 in patients with p16-positive OPSCC. However, within p16-positive OPSCCs, there is an HPV DNA-negative subgroup with distinct features and a worse overall survival, indicating the importance to perform additional HPV DNA testing when predicting prognosis and particularly for selecting patients for de-intensified treatment regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
132
1
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 33 publications
12
132
1
4
Order By: Relevance
“…In the United States, where HPV‐positivity amongst OPSCC patients is very high (70–90% in recent studies), the positive predictive value/correlation with HPV is higher. However, in areas where HPV‐positive rates are lower, such as certain European populations (as low as 20%) and other geographic regions outside of the United States, the positive predictive value is lower, and p16 alone may not be the best approach for classifying patients . Also, up to 26% of nonsquamous, basaloid carcinomas such as solid type adenoid cystic carcinoma, which are not associated with HPV, can be diffusely positive for p16 .…”
Section: Hpv Detection Technologiesmentioning
confidence: 99%
“…In the United States, where HPV‐positivity amongst OPSCC patients is very high (70–90% in recent studies), the positive predictive value/correlation with HPV is higher. However, in areas where HPV‐positive rates are lower, such as certain European populations (as low as 20%) and other geographic regions outside of the United States, the positive predictive value is lower, and p16 alone may not be the best approach for classifying patients . Also, up to 26% of nonsquamous, basaloid carcinomas such as solid type adenoid cystic carcinoma, which are not associated with HPV, can be diffusely positive for p16 .…”
Section: Hpv Detection Technologiesmentioning
confidence: 99%
“…It is well established that p16INK4a (cyclin-dependent kinase 2a) immunohistochemical (IHC) staining can only be a surrogate biomarker of HPV for OPC patients, not for other HNC patients [12]. Accumulating evidence suggests that the importance of additional HPV testing in HPV-associated cancer diagnosis and prognosis [13]. Previous studies have demonstrated that the presence of HPV DNA in tumour tissues is significantly correlated with HPV DNA positivity in saliva samples collected from OPC patients, thus suggesting the use of salivary HPV as a biomarker for the detection of HPV DNA in OPC patients [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the paper by Nauta et al [ 1 ] since it relates to our own experience. The authors described a sub-cohort of oropharyngeal squamous cell carcinomas (OpSCCs) that was p16 positive (+) but HPV DNA negative (−) demonstrating poorer overall survival (OS) compared with p16+/HPVDNA+ individuals.…”
mentioning
confidence: 99%